Concurrent Diffuse Alveolar Hemorrhage, Pleural and Pericardial Effusion Secondary to Propylthiouracil - Sakkat, Abdullah; Amer, Rebecca (Archives of Clinical and Medical Case Reports, 2020)
A 19-year-old woman with trisomy 21 and Graves' disease on propylthiouracil (PTU) admitted to the hospital with a one-month history of fever, cough, pleuritic chest pain and dyspnea. Chest imaging revealed bilateral lower lobe infiltrates, ground-glass opacity, pleural and pericardial effusions. A transthoracic echocardiogram confirmed the presence of circumferential pericardial effusion with constrictive physiology. Serological evaluation was positive for perinuclear anti-neutrophil cytoplasmic antibody (P-ANCA). Bronchoscopy with sequential bronchoalveolar lavage revealed progressively bloodier fluid in keeping with diffuse alveolar hemorrhage (DAH). PTU was discontinued, and prednisone was initiated. This led to complete resolution of clinical, serologic and radiographic abnormalities with no disease recurrence over a 5-year follow-up period. Although DAH, pleural or pericardial diseases are among the reported manifestations of PTU-associated vasculitis, this case is uniquely different from reported cases in the literature where all three manifestations co-occurred. It also has the longest follow-up period.